The curricular planning and its influence on the development of the four linguistic basic skills of the english language in the “National Agricultural Technical High School Gonzanama”, academic year 2009-2010. - Abad Jiménez, Nubia Elizabeth (2010)
The present research about ”THE CURRICULUR PLANNING AND ITS INFLUENCE ON THE DEVELOPMENT OF THE FOUR LINGUISTIC BASIC SKILLS OF THE ENGLISH LANGUAGE IN THE NATIONAL AGRICULTURAL TECHNICAL HIGH SCHOOL GONZANAMA, ACADEMIC YEAR 2009-2010” has been made with the purpose to: determine how the curricular planning influence in the development of the four basic linguistic skills of the English language. In the development of the work we have made use the following methods: descriptive, scientific method, analytic-synthetic method and deductive method. In the field work we applied the instrument of the survey as well to teachers to students. To process the information we have used the logical analysis with the descriptive statistics that helped us to describe the results in tables and graphs. Among the main results of the research we found that the mesoplanning is elaborated by the teachers but they don’t consider the development of the four basic linguistic skills of the English Language. Besides in this institution the teachers don’t plan daily their classes and they don’t take into account in the development of the four skills of the English language. Also in this institution don’t have enough didactic material that permits teachers and students to learn this language in a good way. Finally in this research we found the conclusions and recommendations are considered specifically. The function of language is to communicate ideas by hearing, speaking, reading and writing through intensive practice. This research has been carried on to know the efficacy of daily planning.